Introduction to video production : studio, field, and beyond - Compesi, Ronald J., 1949-; Gomez, Jaime S. (Routledge, 2018)
"Written in a clear, non-technical manner, Introduction to Video Production focuses on the fundamental principles and aesthetics of video production and the technologies used, in both studio and field environments. Ron Compesi and Jaime Gomez cover each aspect of the process step by step, from preproduction to lighting, sound, directing, editing, graphics and distribution. Taking into account the changes in workflow and production planning and distribution brought on by the advent of digital media, this second edition has been updated throughout to account for the increasing popularity of DSLR, online distribution, the rise of portable cameras and mobile video, and much more"--